2009
DOI: 10.1177/1534735409331455
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of an Extract of Emblica officinalis Against Radiation-Induced Damage in Mice

Abstract: The radioprotective effect of Emblica officinalis extract (EOE) was studied in mice. Swiss albino mice were exposed to γ rays (5 Gy) in the absence (control) or presence (experimental) of EOE, orally 100 mg/kg body weight, once daily for 7 consecutive days. A specimen of small intestine (jejunum) was removed from the mice and studied at different autopsy intervals from 12 hours to 30 days. In control animals, crypt cell population, mitotic figures, and villus length were markedly reduced on day 1; these later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…E. officinalis extracts contain various antioxidants such as emblicanin A, emblicanin B, gallic acid, ascorbic acid, ellagic acid which are effective in a range of ailments. Presence of various active phytocompounds bestows Emblica officinalis fruit eaxtract with various therapeutic benefits consequential of radioprotective [14], antiatherosclerotic [20], antidiabetic [21,34], antiaging [38], gastroprotective [1], cytoprotective and immunomodulatory [29] properties (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…E. officinalis extracts contain various antioxidants such as emblicanin A, emblicanin B, gallic acid, ascorbic acid, ellagic acid which are effective in a range of ailments. Presence of various active phytocompounds bestows Emblica officinalis fruit eaxtract with various therapeutic benefits consequential of radioprotective [14], antiatherosclerotic [20], antidiabetic [21,34], antiaging [38], gastroprotective [1], cytoprotective and immunomodulatory [29] properties (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The fruit extract has many pharmacological activities for the treatment of a number of diseases and is a constituent of many hepatoprotective formulations [9]. Several recent reports revealed that fruit extract of Emblica officinalis protect against radiation [10], antiatherosclerosis [11], possess antidiabetic activity [12,13], inhibits aging process [14], gastroprotective [15], cytoprotective and immunomodulatory [16]. Despite its extensive medicinal use no information is available related to its use on alcoholinduced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…On day 15 post-irradiation, the level of lipid peroxidation in liver tissue was also reduced (p<0.001) in group II compared to irradiated control. A latter study supported this effect of EO on lipid peroxidation and antioxidant enzymes (Jindal et al, 2009). In this investigation, the fruit extract of Emblica was administered orally to mice at a concentration of 100 mg/kg b.w., once daily for seven consecutive days before γ-irradiation (5 Gy).…”
Section: Emblica Officinalis Gaertn or Phyllanthus Emblicamentioning
confidence: 88%
“…Radiation-induced inflammation, an important side effect that contributes to normal tissue injury, has been reported in many species (Linard et al, 2004;Fliedner et al, 2005;Kong et al, 2005;Fleckenstein et al, 2007;Haston et al, 2007;Rodemann and Blaese, 2007;Hill et al, 2011;Multhoff and Radons, 2012;Rastogi et al, 2012;Cho et al, 2013;Fu et al, 2013;Jiang et al, 2013;McCurdy et al, 2013;Moore et al, 2013;Mukherjee et al, 2014). The initial phase of radiationinduced injury is marked by the increase in the synthesis of pro-inflammatory cytokines such as transforming growth factor-beta1 (TGF-β1), tumor necrosis factor-alpha (TNF-α) and several other members of interleukin (IL) family (Linard et al, 2004;Fliedner et al, 2005;Kong et al, 2005;Mehta, 2005;Fleckenstein et al, 2007;Haston et al, 2007;Rodemann and Blaese 2007;Jindal et al, 2009;Hei et al, 2011;Janko et al, 2012;Monceau et al, 2013). The hallmark late effect of radiation exposure in several experimental animals is fibrosis, which is often permanent (Han et al, 2006;Lee et al, 2009;Flechsig et al, 2010;Qiu et al, 2011;Gorshkova et al, 2012;Cho et al, 2013;Ding et al, 2013;Horton et al, 2013).…”
Section: Lakhan Kmamentioning
confidence: 99%